2011
DOI: 10.1016/j.jvs.2010.09.055
|View full text |Cite
|
Sign up to set email alerts
|

Carotid endarterectomy in the acute phase of crescendo cerebral transient ischemic attacks is safe and effective

Abstract: Short delay between symptom onset and neurological assessment, immediate start of secondary stroke prevention, optimal perioperative medical treatment, and standardized operative techniques enabled performance of CEA in the acute phase of CcTIAs with low combined risk of stroke, death, and major cardiac event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…26 Likewise our group recently reported no symptomatic intracranial hemorrhage in 64 unstable patients, of whom 78% had a new acute brain infarction on diffusion-weighted MRI, who underwent CEA in the acute phase of crescendo cerebral TIA. 27 Furthermore, with the increasing number of stroke units where thrombolysis is being successfully performed, practitioners will have to manage patients with threatening residual cervical carotid artery stenosis and to reconsider the indications for early CEA. In this particular situation, results from this short series and others are also reassuring.…”
Section: Discussionmentioning
confidence: 99%
“…26 Likewise our group recently reported no symptomatic intracranial hemorrhage in 64 unstable patients, of whom 78% had a new acute brain infarction on diffusion-weighted MRI, who underwent CEA in the acute phase of crescendo cerebral TIA. 27 Furthermore, with the increasing number of stroke units where thrombolysis is being successfully performed, practitioners will have to manage patients with threatening residual cervical carotid artery stenosis and to reconsider the indications for early CEA. In this particular situation, results from this short series and others are also reassuring.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some authors have demonstrated that in unstable patients emergency revascularization complication rates are quite acceptable after a strict patient selection and management protocol. [12][13][14] Currently, the consensus is lacking if unstable patients could benefit from an emergency revascularization procedure.…”
mentioning
confidence: 99%
“…Moreover, patients with a NIHSS ≥8 had a greater reduction on their neurological deficit than those with a lower score at admission. Another recent study confirmed these data by underlining the safety and the efficacy of early surgery in the presence of multiple TIA (crescendo TIAs) owing to carotid stenosis .…”
Section: When To Proceed On Carotid Stenosis After a Stroke Or Tia?mentioning
confidence: 74%